Ground-based Paα narrow-band imaging of local luminous infrared galaxies. II. Bulge structure and star formation activity. (16th May 2019) - Tateuchi, Ken; Motohara, Kentaro; Konishi, Masahiro; Takahashi, Hidenori; Kitagawa, Yutaro; Kato, Natsuko; Todo, Soya; Komugi, Shinya; Ohsawa, Ryou; Doi, Mamoru; Yoshii, Yuzuru
Abstract: We present properties of two types of bulges (classical and pseudobulges) in 20 luminous infrared galaxies observed in the near infrared of the H, K s, and 1.91$μ$ m narrow-band targeting of the hydrogen Paα emission line by the University of Tokyo Atacama Observatory 1 m telescope. To classify the two types of bulges, we first perform a two-dimensional bulge–disk decomposition analysis in the K s -band images. The result shows a tentative bimodal distribution of Sérsic indices with a separation at log ( n b ) ≈ 0.5, which is consistent with that of classical and normal galaxies. We next measure the extents of the distributions of star-forming regions in Paα emission line images, normalized by the size of the bulges, and find that they decrease with increasing Sérsic indices. These results suggest that star-forming galaxies with classical bulges have compact star-forming regions concentrated within the bulges, while those with pseudobulges have extended star-forming regions beyond the bulges, suggesting that there are different formation scenarios at work in classical and pseudobulges.